MIR141 Expression Differentiates Hashimoto Thyroiditis from PTC and Benign Thyrocytes in Irish Archival Thyroid Tissues - Dorris, Emma R.; Smyth, Paul; O'Leary, John J.; Sheils, Orla (Frontiers in Endocrinology, 2012)
MicroRNAs (miRNAs) are small non-coding RNAs approximately 22 nucleotides in length that function as regulators of gene expression. Dysregulation of miRNAs has been associated with initiation and progression of oncogenesis in humans. Our group has previously described a unique miRNA expression signature, including the MIR200 family member MIR141, which can differentiate papillary thyroid cancer (PTC) cell lines from a control thyroid cell line. An investigation into the expression of MIR141 in a series of archival thyroid malignancies (n=140; classic PTC, follicular variant PTC, follicular thyroid carcinoma (FTC), Hashimoto thyroiditis (HT), or control thyrocytes) was performed. Each cohort had a minimum of 20 validated samples surgically excised within the period 1980 - 2009. A subset of the HT and cPTC cohorts (n=3) were also analysed for expression of TGFβR1, a key member of the TGFβ pathway and known target of MIR141. Laser capture microdissection was used to specifically dissect target cells from formalin-fixed paraffin-embedded archival tissue. Thyrocyte- and lymphocyte-specific markers (TSHR and LSP1 respectively) confirmed the integrity of cell populations in the HT cohort. RNA was extracted and quantitative RT-PCR was performed using comparative CT (ΔΔCT) analysis. Statistically significant (p<0.05) differential expression profiles of MIR141 were found between tissue types. HT samples displayed significant downregulation of MIR141 compared to both classic PTC and control thyrocytes. Furthermore, TGFβR1 expression was detected in cPTC samples but not in HT thyrocytes. It is postulated that the down-regulation of this miRNA is due, at least in part, to its involvement in regulating the TGFβ pathway. This pathway is exquisitely involved in T-cell autoimmunity and has previously been linked with HT. In conclusion, HT epithelium can be distinguished from cPTC epithelium and control epithelium based on the relative expression of MIR141.